Overexpression of p53 in extra large (more than 10 cm) hepatocellular carcinoma (Medical Journal of Indonesia, 2018)
Background: Extra large hepatocellular carcinoma (HCC) of >10 cm managed in our center shows a specific characteristic in tropical regions. This type of HCC exhibits distinct p53 expression. This study aimed to determine the association between p53 expression and tumor size and behavior. Method:Subjects with HCC who underwent surgical resection in our hospital during 2012–2015 were enrolled in this study. Subject’s characteristics, tumor size, histopathology findings, and tumor behavior were variables observed. An immunohistochemical study on p53 expression was conducted to determine its association with those variables. Results:This study involved 38 subjects with tumor size ranging from 3 cm to 25 cm in diameter and 20 subjects (52.8%) with tumor size ranging from 10 cm to 25 cm in diameter. Only 13 samples were evaluated for p53 expression. Five subjects with >10 cm (extra large) tumor showed highly/overexpressed p53 (intensity>50%), two subjects with strong p53 expression (intensity>5%–50%), and two subjects with weak expression. Three subjects with <10 cm (large) tumor showed strong expression of p53 (5%–9%) and a subject with 3 cm tumor showed weak p53 expression (<5%). Highly expressed p53 was found in patients with microvascular invasion, inflammatory response, mitosis, and necrosis. Conclusion: Overexpression of p53 was associated with extra large and poorly differentiated HCC.